Prediction Of Closing Price Combined Stock Index (Ihsg) Using The Fuzzy Mamdani Method - Amrul Hinung Prihamayu (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This study proposes a method for predicting the closing IHSG stock price using the Mamdani fuzzy approach. This model uses historical closing stock price data as input, and generates closing stock price predictions using the Mamdani fuzzy rule. However, experimental results show that this model may not be suitable for predicting stock prices accurately and reliably. Therefore, this study does not recommend the use of the Mamdani fuzzy method for the purpose of predicting closing stock prices.